2006
DOI: 10.1021/np050406v
|View full text |Cite
|
Sign up to set email alerts
|

Antiparasitic Activity of Some Xanthones and Biflavonoids from the Root Bark of Garcinia livingstonei

Abstract: A new biflavanoid, ent-naringeninyl-(I-3alpha,II-8)-4'-O-methylnaringenin (6), along with five known xanthones and two known biflavonoids, was isolated from the root bark of Garcinia livingstonei collected in Tanzania. The absolute configuration of 6 was established by CD spectroscopy. This compound showed moderate activity against P. falciparum (IC(50) 6.7 microM). Antitrypanosomal activity (IC(50) 0.87 microM) was observed for 1,4,5-trihydroxy-3-(3-methylbut-2-enyl)-9H-xanthen-9-one (3). The dimeric xanthone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(67 citation statements)
references
References 17 publications
2
61
0
4
Order By: Relevance
“…Sordat-Diserens et al (1992b) isolated the xanthone dimer garcilivin A, which has since been shown to display trypanosomal activity against T. brucei brucei (Mbwambo et al, 2006). Bioassay-guided fractionation of the fruit has yielded the HIV-inhibitory tetraprenylated benzophenone guttiferone A (3) (Gustafson et al, 1992), and the biflavanoid ent-naringeninyl- which is moderately active against a Ghanaian CQS strain of P. falciparum (Mbwambo et al, 2006).…”
Section: Previous Investigations Of This Species Have Resulted In Thementioning
confidence: 99%
See 1 more Smart Citation
“…Sordat-Diserens et al (1992b) isolated the xanthone dimer garcilivin A, which has since been shown to display trypanosomal activity against T. brucei brucei (Mbwambo et al, 2006). Bioassay-guided fractionation of the fruit has yielded the HIV-inhibitory tetraprenylated benzophenone guttiferone A (3) (Gustafson et al, 1992), and the biflavanoid ent-naringeninyl- which is moderately active against a Ghanaian CQS strain of P. falciparum (Mbwambo et al, 2006).…”
Section: Previous Investigations Of This Species Have Resulted In Thementioning
confidence: 99%
“…Sordat-Diserens et al (1992b) isolated the xanthone dimer garcilivin A, which has since been shown to display trypanosomal activity against T. brucei brucei (Mbwambo et al, 2006). Bioassay-guided fractionation of the fruit has yielded the HIV-inhibitory tetraprenylated benzophenone guttiferone A (3) (Gustafson et al, 1992), and the biflavanoid ent-naringeninyl- which is moderately active against a Ghanaian CQS strain of P. falciparum (Mbwambo et al, 2006). Several tree species are used traditionally on the eastern seaboard of South Africa for the treatment of skin diseases and cosmetic purposes, such as for skin lightening, often under the Xhosa and Zulu name umemezi (Earle, 1976;Khan, 1996;Cocks & Dold, 2004;Momtaz et al, 2008).…”
Section: Previous Investigations Of This Species Have Resulted In Thementioning
confidence: 99%
“…Compound TDR13011 (1,2-dihydroxy-6,8-dimethoxy-xanthone) possessed substantial activity against T. b. brucei and moderate activity against L. infantum parasites while compound TDR13008 (1,8-dihydroxy-3,7-dimethoxyxanthone) showed activity only against T. cruzi. Mbwambo et al (2006) have reported varying degrees of antiparasitic activity of five xanthones isolated from the root bark of Garcinia livingstonei against T. b. brucei, T. cruzi and L. infantum while Abe and coworkers (2003) have found antitrypanocidal activity of garciniaxanthone B from Garcinia subelliptica.…”
Section: Resultsmentioning
confidence: 99%
“…Este composto foi isolado de várias espécies de Garcinia (KONOSHIMA et al, 1969(KONOSHIMA et al, , 1970MBWAMBO et al, 2006;VERDI et al, 2004) e a caracterização estrutural e análise conformacional proposta por Li et al (2002) …”
Section: )unclassified
“…A baixa atividade antiparasitária dos biflavonóides em questão está de acordo com as publicações anteriores (MBWAMBO, et al, 2006;WENIGER, et al, 2006 …”
Section: Atividade Tripanocidaunclassified